We kill each other for laziness. On poetry and war - Gimeno, Jorge (2019)
This paper proposes a critic of the traditional notions of pace and war, as well as the very concept of poetry. It analyses the war structure that presides over the civil order and its economic, metaphysical and even poetic dimensions. It is redefined the function of poetry in an attempt to overcome the mere cultural game by restoring its unitive function.